Evaluation of Swimming Learning in PJOK Subjects in Junior High Schools in Tarakan City - Muhammad Zaenuri; Ridho Gata Wijaya (International Journal of Health and Social Behavior, 2025)
Tarakan City as an archipelago with high maritime activity has a significant risk of water accidents, yet students' swimming skills are still low. This study aims to: (1) evaluate the context of swimming learning in the PJOK curriculum, (2) assess input readiness (teachers, facilities, costs), (3) analyze the learning implementation process, and (4) measure learning outcomes related to student skills and safety. The research used a descriptive qualitative approach with the Context, Input, Process, Product (CIPP) evaluation model. Data sources include principals (4 people), physical education teachers (4 people), and students (16 people) from four junior high schools in Tarakan City. The research instruments were semi-structured interview guidelines, observation sheets, and curriculum document analysis. Data collection techniques were conducted through participatory observation, in-depth interviews, and documentation studies. The data were analyzed qualitatively using cost and benefit analysis techniques to identify the suitability of the program to the needs. The results show that the context of swimming learning is in accordance with the curriculum, but the swimming pool facilities depend on public facilities with limited access. The learning process is in accordance with the lesson plan, but the practice time (2 times/semester) is not sufficient to master the skills. Product evaluation results indicated a good understanding of water safety theory, but low practical swimming skills. Recommendations: (1) Increased frequency of swimming practice, (2) collaboration with local government for the provision of school swimming pools, and (3) teacher training in adaptive teaching methods for beginner students.